2022
DOI: 10.48550/arxiv.2203.08830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak Ergodicity Breaking in the Schwinger Model

Abstract: As a paradigm of weak ergodicity breaking in disorder-free nonintegrable models, quantum manybody scars (QMBS) can offer deep insights into the thermalization dynamics of gauge theories. Having been first discovered in a spin-1/2 quantum link formulation of the Schwinger model, it is a fundamental question as to whether QMBS persist for S > 1/2 since such theories converge to the lattice Schwinger model in the large-S limit, which is the appropriate version of lattice QED in one spatial dimension. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 54 publications
2
23
1
Order By: Relevance
“…We have demonstrated this for the spin-S U(1) QLM in Ref. [71] for the extreme vacua. However, this can be seen even more clearly for the TSM, as shown in Fig.…”
Section: S(s + 1)mentioning
confidence: 55%
See 2 more Smart Citations
“…We have demonstrated this for the spin-S U(1) QLM in Ref. [71] for the extreme vacua. However, this can be seen even more clearly for the TSM, as shown in Fig.…”
Section: S(s + 1)mentioning
confidence: 55%
“…This, along with other works proving the existence of quantum many-body scars in various discrete lattice gauge theories [67][68][69] and the necessity of gauge-symmetry stability for their robustness [70], has led to the natural question of whether scars are an inherent feature of "standard" lattice gauge theories with a continuous configuration space. In a recent work by us [71], we have shown that quantum many-body scars persist at larger link spin lengths S > 1/2 in the spin-S U (1) QLM in the form of resonant scarring when the initial state is an extreme vacuum, defined as the most highly excited vacuum state. We have additionally presented evidence of detuned scarring, recently demonstrated experimentally for S = 1/2 [64], also for S > 1/2 when starting in the physical vacuum or the charge-proliferated state.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Scarring also occurs for massive quenches starting in the charge-proliferated state |−1/2, +1, −1/2, +1 , which is the nondegenerate Z 2 -symmetric ground state of Eq. (3) at µ → ∞ and θ = π [63,65,66]. In Sec.…”
Section: Modelmentioning
confidence: 90%
“…Theoretical studies continue to identify large classes of models that exhibit various aspects of QMBS phenomena. Some notable examples include various nonintegrable lattice models [18][19][20][21][22][23][24][25] , models of correlated fermions and bosons [26][27][28][29][30][31][32][33] , frustrated magnets 34,35 , topological phases of matter 36,37 , lattice gauge theories [38][39][40][41][42] , and periodically-driven systems [43][44][45][46][47][48] .…”
mentioning
confidence: 99%

Driving quantum many-body scars

Hudomal,
Desaules,
Mukherjee
et al. 2022
Preprint
Self Cite